LO091: Non-urgent presentations to the emergency department: patients' reasons for presentation. (2nd June 2016) - Krebs, L.; Chetram, R.; Kirkland, S.W.; Nikel, T.; Voaklander, B.; Davidson, A.; Holroyd, B.; Cross, E.; Villa-Roel, C.; Crick, K.; Couperthwaite, S.; Alexiu, C.; et al.
Abstract : Introduction: Some low acuity Emergency Department (ED) presentations are considered non-urgent or convenience visits and potentially avoidable with improved access to primary care. This study explored self-reported reasons why non-urgent patients presented to the ED.Methods: Patients, 17 years and older, were randomly selected from electronic registration records at three urban EDs in Edmonton, Alberta (AB), Canada during weekdays (0700 to 1900). A 47-item questionnaire was completed by each consenting patient, which included items on whether the patient believed the ED was their best care option and the rationale supporting their response. A thematic content analysis was performed on the responses, using previous experience and review of the literature to identify themes.Results: Of the 2144 eligible patients, 1408 (65.7%) questionnaires were returned, and 1402 (65.4%) were analyzed. For patients who felt the ED was their best option ( n = 1234, 89.3%), rationales included: safety concerns ( n = 309), effectiveness of ED care ( n = 284), patient-centeredness of ED ( n = 277), and access to health care professionals in the ED ( n = 204). For patients who felt the EDwas not their best care option ( n = 148, 10.7%), rationales included a perception that: access to health professionals outside the ED was preferable ( n = 39), patient-centeredness (particularly timeliness) was lacking in the ED ( n = 26), and their health concern was not important enough to require ED care ( n = 18).Conclusion: Even during times when alternative care options are available, the majority of non-urgent patients perceived the ED to be the most appropriate location for care. These results highlight that simple triage scores do not accurately reflect the appropriateness of care and that understanding the diverse and multi-faceted reasons for ED presentation are necessary to implement strategies to support non-urgent, low acuity care needs.